2009
DOI: 10.1007/s00269-008-0285-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviour and kinetics of dehydration of gypsum in air from in situ real-time laboratory parallel-beam X-ray powder diffraction

Abstract: Thermal behaviour and kinetics of dehydration of gypsum in air have been investigated using in situ real-time laboratory parallel-beam X-ray powder diffraction data evaluated by the Rietveld method. Thermal expansion has been analysed from 298 to 373 K. The high-temperature limits for the cell edges and for the cell volume, calculated using the Einstein equation, are 4.29 x 10(-6), 4.94 x 10(-5), 2.97 x 10(-5), and 8.21 x 10(-5). Thermal expansion of gypsum is strongly anisotropic being larger along the b axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 37 publications
1
53
3
Order By: Relevance
“…Giustling-Brounsthein (D4) The difference in DTG and DTA profiles, among two PG, indicates the influence of sample origin, chemical composition and traces on dehydration behavior (28). The most obvious discrepancy is the temperature, at which gypsum begins to dehydrate.…”
Section: Thermal Behaviour Of Phosphogypsummentioning
confidence: 99%
See 2 more Smart Citations
“…Giustling-Brounsthein (D4) The difference in DTG and DTA profiles, among two PG, indicates the influence of sample origin, chemical composition and traces on dehydration behavior (28). The most obvious discrepancy is the temperature, at which gypsum begins to dehydrate.…”
Section: Thermal Behaviour Of Phosphogypsummentioning
confidence: 99%
“…Most literature reported that gypsum dehydration undergoes a two-step process, via hemihydrate (25,28,(42)(43)(44), while some reports showed that γ-CaSO 4 is directly produced during gypsum dehydration of γ-CaSO 4 upon cooling with humidity air (45 (48) reported that under non-isothermal conditions and in two steps, via hemihydrate in "autogenous P H 2 O ", the dehydration of the gypsum contained in the "flue gas desulfurization gypsum (FGDG) occurs in one step (CaSO 4 2H 2 O→γ-CaSO 4 ), when the P H 2 O is negligible.…”
Section: Thermal Behaviour Of Phosphogypsummentioning
confidence: 99%
See 1 more Smart Citation
“…The (force) fitted data are then used to determine the dimensionality of the single 'rate-determining step ' (e.g. Bray and Redfern 2000;Cattaneo et al 2003;Perrillat et al 2005;Ferrage et al 2007;Carbone et al 2008;Ballirano and Melis 2009;Chollet et al 2009;Inoue et al 2009;Tokiwai and Nakashima 2010;Gualtieri et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1 filter paper; the filter cake was thoroughly rinsed with water, dried at mild temperature (i.e 60° C; to prevent thermal conversion of gypsum [19]) for 24 h and characterized by XRD and high-vacuum SEM. Throughout the experiments, sub-samples of the suspensions were collected from the reactor at regular intervals and filtered using 0.45µm PALL acrodisc PSF GxF/GHP membranes (Microsep (Pty) Ltd, South Africa).…”
Section: Direct Aqueous Carbonation Experimentsmentioning
confidence: 99%